Preclinical Modeling and Therapeutic Avenues for Cancer Metastasis to the Central Nervous System - Singh, Mohini; Bakhshinyan, David; Venugopal, Chitra; Singh, Sheila K. (Frontiers in Oncology, 2017)
Metastasis is the dissemination of cells from the primary tumor to other locations within the body, and continues to be the predominant cause of death among cancer patients. Metastatic progression within the adult central nervous system is ten times more frequent than primary brain tumors. Metastases affecting the brain parenchyma and leptomeninges are associated with grave prognosis, and even after successful control of the primary tumor the median survival is a dismal 2-3 months with treatment options typically limited to palliative care.. Current treatment options for BM and disseminated brain tumors are scarce, and the improvement of novel targeted therapies requires a broader understanding of the biological complexity that characterizes metastatic progression. In this review, we provide insight into patterns of BM progression and leptomeningeal spread, outlining the development of clinically relevant in vivo models and their contribution to the discovery of innovative cancer therapies. In vivo models paired with manipulation of in vitro methods have expanded the tools available for investigators to develop agents that can be used to prevent or treat metastatic disease. The knowledge gained from the use of such models can ultimately lead to the prevention of metastatic dissemination and can extend patient survival by transforming a uniformly fatal systemic disease into a locally controlled and eminently more treatable one.